Klasyczna proweniencja zwierzęcych metafor w „De civilitate morum puerilium” Erazma z Rotterdamu - Chudzikowska-Wołoszyn, Małgorzata (Echa Przeszłości, 2018)
The main aim of this article was to classify the animalistic metaphors used by Erasmus of Rotterdam in his moral treatise De civilitate morum puerilium. For Era-smus, a metaphor was the main rhetorical fgure whose clarity and transparency sup-ported the infnite penetration of truth. The classical provenance of the animalistic symbols in the treatise was traced back to analyse the author’s animalistic phraseolo-gy. Attempts were made to determine the semantic space and the essential signifcan-ce of animalistic symbols. Special emphasis was placed on the rationale behind the use of animalistic domains in the literary perspectives selected by Erasmus.